d/dx tan⁻¹ √1+x²-√1-x²/√1-x²+√1+x²=......... | x | < 1 ,Select Proper option from the given options.
(a) 1/√1-x⁴
(b) -x/√1-x⁴
(c) 1/2√1-x⁴
(d) x²/1-x⁴
Answers
Answered by
1
I hope this helps ya
Answered by
4
we have to find value of ![\frac{d}{dx}tan^{-1}\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}} \frac{d}{dx}tan^{-1}\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7Dtan%5E%7B-1%7D%5Cfrac%7B%5Csqrt%7B1%2Bx%5E2%7D-%5Csqrt%7B1-x%5E2%7D%7D%7B%5Csqrt%7B1%2Bx%5E2%7D%2B%5Csqrt%7B1-x%5E2%7D%7D)
Let![y=tan^{-1}\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}} y=tan^{-1}\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}}](https://tex.z-dn.net/?f=y%3Dtan%5E%7B-1%7D%5Cfrac%7B%5Csqrt%7B1%2Bx%5E2%7D-%5Csqrt%7B1-x%5E2%7D%7D%7B%5Csqrt%7B1%2Bx%5E2%7D%2B%5Csqrt%7B1-x%5E2%7D%7D)
![tany=\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}} tany=\frac{\sqrt{1+x^2}-\sqrt{1-x^2}}{\sqrt{1+x^2}+\sqrt{1-x^2}}](https://tex.z-dn.net/?f=tany%3D%5Cfrac%7B%5Csqrt%7B1%2Bx%5E2%7D-%5Csqrt%7B1-x%5E2%7D%7D%7B%5Csqrt%7B1%2Bx%5E2%7D%2B%5Csqrt%7B1-x%5E2%7D%7D)
squaring both sides,
tan²y =![\frac{1-\sqrt{1-x^4}}{1+\sqrt{1-x^4}} \frac{1-\sqrt{1-x^4}}{1+\sqrt{1-x^4}}](https://tex.z-dn.net/?f=%5Cfrac%7B1-%5Csqrt%7B1-x%5E4%7D%7D%7B1%2B%5Csqrt%7B1-x%5E4%7D%7D)
(1 - tan²y) = √(1 - x⁴) (tan²y + 1)
(1 - tan²y)/(tan²y + 1) = √(1 - x⁴)
(1 - tan²y)/sec²y = √(1 - x⁴)
cos²y - sin²y = √(1 - x⁴)
cos2y = √(1 - x⁴) [ we know, cos2r = cos²r - sin²r]
now , differentiate with respect to x,
![-2sin2y. dy/dx = \frac{1}{\sqrt{1-x^4}}(-2x^3) -2sin2y. dy/dx = \frac{1}{\sqrt{1-x^4}}(-2x^3)](https://tex.z-dn.net/?f=-2sin2y.+dy%2Fdx+%3D+%5Cfrac%7B1%7D%7B%5Csqrt%7B1-x%5E4%7D%7D%28-2x%5E3%29)
we know, sin2y = 2tany/(1 + tan²y)
= 2{√(1 + x²) - √(1 - x²)}{√(1 + x²) + √(1 - x²)}/[{√(1-x²) + √(1 + x²)}² + {√(1 + x²) - √(1 - x²)}²]
= 4x²/{2 + 2√(1 - x⁴) + 2 - 2√(1 - x⁴)}
= 4x²/4
= x² hence, sin2y = x²
now, -2x². dy/dx = -2x³/√(1 - x⁴)
dy/dx = x/√(1 - x⁴)
Let
squaring both sides,
tan²y =
(1 - tan²y) = √(1 - x⁴) (tan²y + 1)
(1 - tan²y)/(tan²y + 1) = √(1 - x⁴)
(1 - tan²y)/sec²y = √(1 - x⁴)
cos²y - sin²y = √(1 - x⁴)
cos2y = √(1 - x⁴) [ we know, cos2r = cos²r - sin²r]
now , differentiate with respect to x,
we know, sin2y = 2tany/(1 + tan²y)
= 2{√(1 + x²) - √(1 - x²)}{√(1 + x²) + √(1 - x²)}/[{√(1-x²) + √(1 + x²)}² + {√(1 + x²) - √(1 - x²)}²]
= 4x²/{2 + 2√(1 - x⁴) + 2 - 2√(1 - x⁴)}
= 4x²/4
= x² hence, sin2y = x²
now, -2x². dy/dx = -2x³/√(1 - x⁴)
dy/dx = x/√(1 - x⁴)
flower161:
nice answer
Similar questions